Selective Serotonin Reuptake Inhibitors: How Long Is Long Enough?. Issue 5 (September 2021) - Thom, Robyn P.; Alexander, Jeanne L.; Baron, David; Garakani, Amir; Gross, Lawrence; Pine, Janet H.; Radhakrishnan, Rajiv; Slaby, Andrew; Sumner, Calvin R.
Abstract : Selective serotonin reuptake inhibitors (SSRIs) are among the most commonly prescribed medications. They are among the first-line medications for several chronic or relapsing-remitting psychiatric conditions, including major depressive disorder and anxiety disorders. The advantages of SSRI use include ease of titration and their tolerability and safety profile. Guidelines for the short-term use of SSRIs are widely available, but there is no well-organized guidance on how and whether to maintain a patient on SSRIs for the long-term. In this article, we discuss the benefits and possible adverse consequences of long-term SSRI use, as well as clinical practice considerations when using SSRIs chronically. The major benefit of long-term SSRI use is relapse prevention. The current literature suggests that the general health risks of long-term SSRI use are low; however, further research, particularly in special populations including youth and the elderly, is needed. Long-term SSRI use increases the risk of tachyphylaxis and discontinuation syndrome. Recognizing that many patients may remain on SSRIs for many years, there are several factors that prescribers should consider if they choose to use an SSRI when initiating treatment and during long-term monitoring. The decision to continue or to discontinue an SSRI should be an active one, involving both the patient and prescriber, and should be revisited periodically. Patients who remain on SSRIs for the long-term should also have periodic monitoring to reassess the risk-benefit ratio of remaining on the SSRI, as well as to assess the safety, tolerability, and efficacy of the medication.